Reliable Establishment of Human Sarcoma Xenografts in the Nude Rat. (1999) - Tinkey, Peggy T.; Milas, Mira; Pollock, Raphael E.
Abstract : Purpose. The ability to establish consistent human tumor xenografts in experimental animals is a crucial part of preclinical investigations.The goal of this study was to develop a method of establishing a human tumor xenograft in the leg of a nude rat for evaluation of new surgical and molecular methods of treatments of human extremity sarcoma. Methods and results. Initial attempts to produce sarcoma nodules by subcutaneous injection of a human leiomyosarcoma tumor cell suspension (SKLMS-1) resulted in tumor nodule formation in only four of 10 sites (40%).The xenograft method was modified to include younger nude rats of a different source and substrain (HSD:rnu/rnu, 5–9 weeks old), treated with 500 cGy whole-body irradiation, and the transplantation of tumor cells or small tumor fragments which had been embedded in Matrigel.These changes improved the tumor take rate per site to 52/52 (100%).Tumor nodules demonstrated rapid and progressive growth and histological features consistent with the original human sarcoma. Discussion. Successful human leiomyosarcoma establishment in these nude rats permits the investigation of sarcoma biology and treatment with surgical procedures for which a mouse model would be inadequate. In this study we identified modifications in technique which enhanced the xenografting of a leiomyosarcoma cell line in nude rats; these techniques may increase tumor take rates for other tumor types as well.